Sam Fox Collection of Semi Classics for Orchestra, Vol. 1 - O'hara, Geofrey (Sam Fox pub. co., 1922)
Buku ini terdiri dari lagu: I love a little cottage, out of the dusk to you, my heart is waiting, only snile, i love you ore, lassie o' mine, one fleeting hour, I'm a-longin' fo' you, only a year ago, my dreams, ship o'dremas, think love of me, just like your eyes, i gathered a rose